AI powered automated valuation models : A case study on the Finnish rental market - Koskela, Tatu (My University, 2024)
Residential real estate, due to its heterogenous nature, does not have stock markets. The lack of accurate and real-time price information necessitates the use of costly manual appraisals. Even if appraised, the true value of every piece of property is not certain until sold. The same applies to rental contracts for these properties. Automated valuation models present a possible remedy to reduce appraisal costs and improve accuracy of rental contract pricing. However, the use of automated valuation models is prone to numerous pitfalls. The intent of this study is to overcome these challenges and build an automated valuation model to appraise the market rents of residential real estate properties. The dataset consists of a collection of rental listings collected from a Finnish rental residential real estate portal. To build the model, we used open-source libraries such as Keras, Scikit and Tensorflow to build an artificial neural network regression model. We then tested various architectures over time to find the best performing model. The best model achieved an r2 of 0.89 and a mean absolute percentage error of 5.75. We used several models from other studies as a benchmark for our model’s performance. Our model achieved superior performance compared to the benchmark models. However, this superior performance is not necessarily due to better methodology but can also be explained with other factors such as betterquality data and narrower scope. Finally, we selected the best performing model to act as a production model. This model, over a period of a year and a half, was refreshed with new data as it was collected. The accuracy did not drift significantly over time.

Kiinteistömarkkinoille ei ole olemassa pörssiä, kuten osakkeille, niiden heterogeenisyyden vuoksi. Siksi kiinteistöjen arvoon liittyy epävarmuutta, joka ratkeaa vasta myynnin yhteydessä. Kiinteistöjen vuokrasopimuksiin pätee sama epävarmuus. Kiinteistöjen arvonmääritys ja markkinavuokrien arviointi manuaalisesti on kuitenkin kallista. Automaattiset hinnoittelumallit tarjoavat mahdollisuuden vähentää vuokrien arviointiin liittyviä kustannuksia, ja mahdollisesti myös parantaa tarkkuutta. Automaattiset hinnoittelumallit ovat kuitenkin alttiita monille ongelmille, jotka rapauttavat tai jopa kokonaan tuhoavat niistä saadut hyödyt. Tämän tutkielman tavoite on rakentaa tekoälyä hyödyntäen automaattinen hinnoittelumalli, joka onnistuu arvioimaan asuntojen vuokria. Aineisto koostuu vuokrailmoituksista, jotka on kerätty eräältä vuokra-asuntojen ilmoitussivustolta. Rakensimme aineiston perusteella syväoppivan tekoälyregressiomallin. Mallin rakentamiseen käytimme avoimen lähdekoodin kirjastoja, kuten Keras, Scikit ja Tensorflowia. Testasimme useita eri arkkitehtuureja, joista paras saavutti r2 arvon 0,89 ja keskimäärisen absoluuttisen prosenttipoikkeaman 5,75. Käytimme muutaman toisen tutkimuksen malleja vertailukohteina mallillemme. Paras mallimme ylitti vertailumallien tarkkuuden selvästi. Tämä ei kuitenkaan välttämättä ole metodiemme tai paremman arkkitehtuurin ansiota – parempi tarkkuus on myös selitettävissä esimerkiksi laadukkaammalla datalla ja tekemillämme rajauksilla. Lopuksi valitsimme parhaan arkkitehtuurin pitkäaikaiseen testaukseen. Datan keräys jatkui, ja tätä mallia koulutettiin uudella datalla noin puolentoista vuoden ajan. Mallin tarkkuus ei olennaisesti muuttunut tällä ajalla.
Keywords: artificial intelligence, regression, real estate, rent, finance, pricing, valuation, tekoäly, regressio, vuokra-asunnot, hinnoittelu, laskentatoimi, rahoitus, arvonmääritys